Capitalism and socialism : a theological inquiry - Novak, Michael (Washington : American Enterprise Institute for Public Policy Research, 1979)
This book examines capitalism and socialism and how religion and theology are incorporated into their definitions.
"The conference from which this volume stems was held at Airlie House, in Warrenton, Virginia, from July 9 to 16, 1978."
Bibliography: p. 187-190.
aia 26/10/17
Loans
Keywords: Socialism; Capitalism; Theology